KENDALA PENGEMBANGAN INOVASI PADA PEMERINTAH DAERAH KABUPATEN CILACAP - Satwika Wijaya, Shadu (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
In an effort to encourage good governance, strong commitment and consistency are needed in efforts to improve sustainable development. In the context of decentralization and regional autonomy, the ability to develop innovation is needed in various aspects, especially public services, development, empowerment and improving community welfare at the regional level. One of the important steps that regional governments need to take at this time is to accelerate regional development through the implementation of regional innovation. Strengthening Regional Innovation is the main strategy within the National Innovation System framework, which facilitates integration between elements of strengthening the innovation system at the macro level and industrial sectors in the local context. The development of this innovation system is in line with the national agenda, through innovation that is directed with the right strategy and strong commitment. However, efforts to develop innovation in government organizations still face obstacles. Therefore, this research aims to identify potential obstacles that the Cilacap Regency Regional Government may face in its efforts to develop innovation. Through this research, it is hoped that it can help identifying effective solutions to increase regional government innovation capabilities, improve services to the community, and support regional economic growth. This research was carried out in Cilacap Regency with the Cilacap Regency Government as the research subject. This research uses a quantitative approach with data collected through survey techniques. The research results show that the potential for innovation and innovation policies already exists, as well as encouragement to motivate, but the formation of optimal Work Teams and improving the innovation ecosystem which has not yet reached the optimal level are the main obstacles.